The State of Institutional Readiness to Build Regional One Data to Foster Data-Driven Policy: Experience from Garut Regency Office of Industry, Trade, Energy, and Mineral Resources - Rifai , Bahtiar; Sari, Karlina; Soekarni , Muhammad; Septian, Adityawati (Universitas Muhammadiyah Yogyakarta, 2025)
Digitising government data has been a critical challenge for sub-national governments in implementing Open Government Data since there is a gap between top-down policy implementation and the bottom-up data flow from the local to the national level. Sub-national government offices encounter issues providing quality, complete, sufficient, and timely updates to government data. Investigating institutional readiness is one of the fundamental stages among the key factors determining OGD implementation to foster data-driven policy. This study aims to measure the institutional readiness of the Garut Regency Office of Industry, Trade, Energy, and Mineral Resources (OITEMR) in developing small and medium industry (SMI) databases. The readiness level is assessed based on five pillars: Policy and Regulation, Data Management, Data Utilization, Human Resources, and Infrastructure. The study employed a questionnaire survey of 42 local government staff and a focus group discussion. The result shows that the readiness state of the OITEMR is at level 2 with an average score of 1,83 out of 5, which means the Office is still at the basic stage of establishing an OGD. Human resources capability and digital infrastructure capacity are the lowest readiness state among the five pillars. The study suggests that top-down policy for implementing OGD should be responsive to situations at sub-national government offices that lack data knowledge, digital capacity, skilled human resources, and financial budget. The study contributes to academic knowledge by elaborating theoretical and practical approaches to develop an institutional readiness index applied at the sub-national government's Office where government data is produced.